1999
DOI: 10.1177/107769909907600311
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere Near Picture Perfect: Images of the Elderly in Life and Ebony Magazine Ads, 1990–1997

Abstract: This content analysis of Life and Ebony, which replicates and updates an earlier study, examines 9,314 advertisements and shows that fewer elderly figures appeared in the magazines than during the previous decade. Further, the figures that did appear more often are associated with aging products and services. A surprising finding was that African-American elderly figures in Life appeared proportionately more than White elderly figures in Ebony. This is the opposite of what was found in a previous study. If mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This suggests that the under-and misrepresentation of older adults in the media (Bramlett-Solomon & Subrananian, 1999;Bramlett-Solomon & Wilson, 1989;Chinen, 1985;de Luce, 2001;Kessler et al, 2004;Signorielli, 2004;Vernon et al, 1990) is a missed opportunity for improving expectations regarding aging. If such a brief exposure to positive aging was able to have an impact, at this point one can only imagine what the influence of longer or repeated exposure may have on aging related expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the under-and misrepresentation of older adults in the media (Bramlett-Solomon & Subrananian, 1999;Bramlett-Solomon & Wilson, 1989;Chinen, 1985;de Luce, 2001;Kessler et al, 2004;Signorielli, 2004;Vernon et al, 1990) is a missed opportunity for improving expectations regarding aging. If such a brief exposure to positive aging was able to have an impact, at this point one can only imagine what the influence of longer or repeated exposure may have on aging related expectations.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the proportion of older adults in the population significantly exceeds the proportion of older adults in prime time television. Numerous other studies examining various forms of popular culture, which include media as well as fictional books directed at narrower audiences, echo the conclusion that older adults are underrepresented (Bramlett-Solomon & Subrananian, 1999;Bramlett-Solomon & Wilson, 1989;Chinen, 1985;de Luce, 2001;Kessler, Rakoczy, & Staudinger, 2004;Vernon, Phillips, Williams, & Wilson, 1990).…”
mentioning
confidence: 95%
“…The percentage of older people used in advertisements is far less than their actual population percentage (Bramlette-Solomon & Subramanian, 1999;Gantz, Gartenberg, & Rainbow, 1980;Harris & Feinberg, 1977;Hiemstra, Goodman, Middlemiss, Vosco, & Ziegler, 1983;Moore & Cadeau, 1985;Peterson, 1992;Robinson, 1998;Robinson, Duet & Smith, 1995;Swayne & Greco, Offensive Senior Stereotypes 505 1987;Ursic, Ursic, & Ursic, 1986). When older individuals are placed in an advertisement, they are usually shown with a number of other ''younger'' adults, which is a direct reflection of advertisers' lack of confidence in this market (Bramlette-Solomon & Subramanian, 1999;Gantz, et al, 1980;Robinson et al, 1995;Smith, 1976;Swayne & Greco, 1987;Ursic et al, 1986). Older males are far more likely to appear in advertisements than older females (Gantz et al, 1980;Harris & Feinberg, 1977;Hiemstra et al, 1983;Robinson et al, 1995;Robinson, 1998;Swayne & Greco, 1987;Ursic et al, 1986).…”
mentioning
confidence: 99%
“…Older males are given more powerful roles, like the wise patriarch or an authority figure, and older females are portrayed most often ''as useful accoutrements to males'' (Davis & Davis 1985, p. 47). Seniors do advertise a variety of products; however, most tend to deal with health, food, consumer services, and household products (Bramlette-Solomon & Subramanian, 1999;Swayne & Greco, 1987;Ursic et al, 1986). Robinson (1998) found that in television, magazine, and newspaper advertisements targeting the older market, 85% were for health-related products.…”
mentioning
confidence: 99%
See 1 more Smart Citation